When market forces backfire: Mandatory ESG disclosure and corporate innovation - ZHANG, Andi (Institutional Knowledge at Singapore Management University, 2024)
Mandatory ESG disclosure makes it possible to incorporate ESG information into stock prices, incentivizing firms to “do good”. This channel, however, may lead to suboptimal investments, according to disclosure theories. This study investigates the changes in firms’ investment in innovation activities following the staggered introduction of mandatory ESG disclosure around the world. Using a sample of corporate patents filed by listed firms across 58 countries from 2000 to 2022, I find that the introduction of mandatory ESG disclosure is associated with less corporate innovation. The effect is mainly driven by countries that mandate ESG disclosure within corporate financial reports, when the market force channel is more likely to work (i.e., when ESG information is more likely to be incorporated into stock prices). To shed light on the underlying mechanism, I document a less sensitive market response to financial information, measured by a reduction in earnings response coefficients (ERCs) and the main effect is mainly driven by countries with a greater reduction in ERCs. In addition, the main effect is partially mitigated in countries with stronger external financing and unlikely to be driven by proprietary cost. Collectively, this paper suggests that mandatory ESG disclosure leads to an unintended cost for corporate innovation.